Model Test on the Influence of Surcharge, Unloading and Excavation of Soft Clay Soils on Shield Tunnels - Pengfei Xiang (MDPI AG, 2021)
In view of the influence of symmetrical surcharge, unloading and excavation of soft clay soils on shield tunnels, the surface settlement, tunnel settlement, vertical additional earth pressure and tunnel additional confining pressure are measured by an indoor model test. The changes of confining pressure, tunnel settlement, surface settlement and vertical earth pressure caused by surcharge, unloading and excavation are studied and analyzed. The results show that, in soft clay, surcharge will cause tunnel settlement, and unloading and excavation will generally cause tunnel uplift. There is hysteresis in surface settlement and tunnel settlement above the shield tunnel caused by surcharge and unloading; the change of additional confining pressure of the shield tunnel caused by surcharge is mainly concentrated in the three directions of 3, 5 and 7 of the radar chart. These points belong to weak points. Unloading and excavation can effectively reduce the additional confining pressure of the tunnel in these three directions; excavation will cause the increase of vertical cumulative additional earth pressure and tunnel confining pressure in local directions. The influence range of surcharge in soft clay is wider than that in sand, but the depth is relatively shallow.